2023
DOI: 10.1093/schbul/sbac202
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolic Profile in Schizophrenia Patients With Antipsychotic-Induced Constipation and Its relationship With Gut Microbiome

Abstract: Background and Hypothesis Antipsychotics (APs), the cornerstone of schizophrenia treatment, confer a relatively high risk of constipation. However, the mechanisms underpinning AP-induced constipation are poorly understood. Thus, we hypothesized that (1) schizophrenia patients with AP-induced constipation have distinct metabolic patterns; (2) there is more than one mechanism at play in producing this adverse drug effect; and (3) AP-associated changes in the gut microbiome are related to the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…Because a decrease in fecal hardness leads to the prevention of constipation, it is hypothesized that dietary glucosylceramide may exert its physiological effects by preventing constipation. Studies have shown that antipsychotic-induced constipation can interfere with sphingolipid metabolism, choline metabolism, and the sphingolipid signaling pathway [ 57 ]. However, these hypotheses should be verified in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Because a decrease in fecal hardness leads to the prevention of constipation, it is hypothesized that dietary glucosylceramide may exert its physiological effects by preventing constipation. Studies have shown that antipsychotic-induced constipation can interfere with sphingolipid metabolism, choline metabolism, and the sphingolipid signaling pathway [ 57 ]. However, these hypotheses should be verified in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The liquid chromatography-electrospray ionization-mass spectrometry (LC-ESI-MS/MS) is a rapidly evolving analytical technique and one of the most sensitive methods in metabolomic research, providing structural and quantitative information in the identification of peptides, lipids, carbohydrates, and other metabolites in biological samples [5]. Previous metabolomic studies of biological materials (blood, urine, saliva, hair) from patients with schizophrenia [17][18][19][20][21][22] highlight the role of metabolites as potential biomarkers for schizophrenia. Metabolomic analysis of biological samples from patients based on LC-ESI-MS/MS is providing an increasing number of new disease biomarkers [23].…”
Section: Introductionmentioning
confidence: 99%